Acoustic performance of countersunk micro-perforated panel in multilayer porous material. Issue 1 (March 2020) - Yuvaraj, L; Jeyanthi, S
This study investigates the acoustic performance of a countersunk micro-perforated panel, along with two distinct porous materials used in a multilayer porous absorber configuration. Additive manufacturing is applied to create sub-millimeter perforation with different hole spacings on polymer micro-perforated panels. Experiments are conducted in an impedance tube, in which the effects of the perforation ratio, air gap, and varying porous layer configurations on the sound absorption capabilities are investigated. For validation, considering the converging hole profile in the micro-perforated panel, an integration method with end correction is used to calculate the tapered section impedance, and the traditional Maa theory is used for the uniform hole. The theoretical impedance of the multilayer absorber is calculated using the transfer matrix method and subsequently compared to the experimental results. The results demonstrate that the countersunk hole micro-perforated panel exhibits a significant improvement in sound absorption, and the introduction of porous materials extends the sound absorption bandwidth. Furthermore, the results indicate that the sound absorption capability depends on the porous material placement in the multilayer absorber configuration.